Aktivitas Amilase dan Laju Metabolisme Ikan Lele Dumbo (Clarias gariepinus) pada Kondisi Puasa dan Pemberian Pakan Kembali - Esti Dwi Pratiwi; Untung Susilo; Slamet Priyanto (Fakultas Biologi | Universitas Jenderal Soedirman, 2013)
The study to determine amylase activity and metabolic rate of catfish, Clarias gariepinus under starvation and refeeding conditions has been conducted with three treatments and four replications in randomized completely design. The result showed that the amylase activity was significant different (P<.05) only at second week after treatment and metabolic rate was significant different (P<.050 at first and second week after treatment. Conclutions, the amylase activity and metabolic rate of catfish have been decreased at starvation, especially at second week, but it recovery at refeeding condition.